A Firm-Level Analysis Of The Relationship Between Gasoline Prices, Oil Prices and the Returns of Chinese Stocks - Wang, Hongtai (2020)
The fluctuation of international oil price has comprehensive impacts on almost every aspects of the economy. Specifically, the oil price shock effect would increase the cost of an industry. Although there are several studies investigating the impact of oil price shocks from the macro perspectives, such as the industry level or the market level, firm-level analysis is still rare. This study combines the Fama-three-factor asset pricing model with energy features to estimate the impacts of energy price shocks on 1493 Chinese companies from 2005 to 2020. Many previous studies only used the oil price shocks as a single indicator to proxy the energy price shocks. However, when the gasoline price is strongly controlled by the government in China, the oil price is unable to fully represent the variation of the whole energy market. Hence, an important contribution of this paper is to include the domestic gasoline price shocks into the analytic framework. After integrating the oil and gasoline price shocks into the model, we find that the Chinese gasoline policy seems to be unable to reduce the fluctuation in the financial market as expected.